2020
DOI: 10.1038/s41366-020-00680-7
|View full text |Cite
|
Sign up to set email alerts
|

Can reduction in infection and mortality rates from coronavirus be explained by an obesity survival paradox? An analysis at the US statewide level

Abstract: Coronavirus disease 2019 (COVID-19) is a declared global pandemic with multiple risk factors. Based on recent empirical studies, obesity is considered by several researchers as one of the serious risk factors for coronavirus-related complications. Yet, other scholars argue in favor of the existence of an obesity survival paradox. The objective of the current study is to analyze the potential relationships between different corona indicators and obesity on a statewide level. Since the United States is ranked as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…However, regarding obesity, contradictory results–obesity paradox-were reported in previous studies [ 15 ]. Similarly, there was a recent study on ‘an obesity survival paradox’ that authors showed the projected rates of COVID-19 infection and mortality drop with elevated prevalence of obesity in United States [ 26 ]. However, in the current COVID-19 pandemic, the majority of studies reported obesity as a risk factor for progressing to severe COVID-19 and were associated with the need for hospitalization and admission to the critical care unite due to COVID-19 [ 7 , 17 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, regarding obesity, contradictory results–obesity paradox-were reported in previous studies [ 15 ]. Similarly, there was a recent study on ‘an obesity survival paradox’ that authors showed the projected rates of COVID-19 infection and mortality drop with elevated prevalence of obesity in United States [ 26 ]. However, in the current COVID-19 pandemic, the majority of studies reported obesity as a risk factor for progressing to severe COVID-19 and were associated with the need for hospitalization and admission to the critical care unite due to COVID-19 [ 7 , 17 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…(1) and (2). While columns (1), ( 3) and (5) give the random effect regression outcomes for the dependent variable Y 1 ¼ BMI, columns (2), ( 4) and ( 6) provide the outcomes for the dependent variable Y 2 ¼ lnðBMIÞ. This logarithmic transformation gives a percent approximation between projected BMI of Hebrew speakers (the base category) vs. that of the native Arab speakers and that of the age.…”
Section: Between-group Comparisonmentioning
confidence: 99%
“…(3) and (4). While columns (1), ( 3) and (5) give the random effect regression outcomes for the dependent variable Y 1 ¼ BMI, columns (2), ( 4) and (6) provide the outcomes for the dependent variable Y 2 ¼ lnðBMIÞ. Once again, at the bottom of table, we report the results of the F-statistics that all elements of d !…”
Section: Between-group Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the comorbidities, the terms "obesity" and "malnutrition" "as defined by the clinical staff " are registered in the case record form, but not the body mass index as an objective measure of obesity. Whether obesity influences the prognosis in COVID-19 is a still controversially assessed issue, and it is uncertain whether ethnic and socioeconomic differences might play a role for the discrepant findings (15)(16)(17).…”
Section: Missing Baseline Informationmentioning
confidence: 99%